CAPTURING THE PROCESS OF NORMATIVE COMMITMENT THROUGH ESTABLISHING PROFESIONALISM OF TEACHER BASED ON PESANTREN - Hasanah, Uswatun; Sapuding, Bayyina; Agus R, Abu Hasan (Nurul Jadid University, 2023)
This research aims to find out how committed the teaching staff at the Nurul Jadid Pesantren are to efforts to improve the quality of education, especially in the context of forming a superior generation. Work commitment is a key factor in the success of educational institutions, and improving the quality of education is the main goal in preparing a generation that is able to compete in the current global era. Thus, this research employs a qualitative approach with a case study design. Data collection is conducted using observation techniques, in-depth interviews, and documentation. The gathered data is analyzed using Miles and Huberman's data analysis techniques, which consist of data reduction, data display, and verification. The research findings indicate that efforts to build normative-based professionalism are carried out in the form of; 1) human resource education with superior paradigm; 2) fostering a culture of quality habituation; 3) self-development optimization; and 4) strengthening spiritual values.